Performance management system of hospitality management department of Cebu Technological University campuses - de la Cruz Ronald; Minoza Joemar; Zosa Leo (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
This research study assessed the performance management system of the Hospitality Management Department of Cebu Technological University. This study employed a descriptive survey method which targets Administrators and Faculty members of Cebu Technological University as respondents who were chosen purposively. A survey questionnaire was utilized to generally assess the extent of the practice of the performance management system of the Hospitality Management of nine (9) Cebu Technological University campuses. It was found out that Cebu Technological University has implemented all indicators of a performance management system that includes performance planning, performance monitoring, performance evaluation, performance development, and performance recognition at all times as assessed by Administrators and Faculty Members, and there was a significant mean difference in the assessment of the two groups of respondents. It was concluded that Cebu Technological University is an organization that regularly implements all aspects and indicators of the performance management system. This corroborates William’s Performance Management Principle that stated that “what gets measured gets done, what gets managed gets done better and what gets rewarded gets done sooner” (Williams, 1998, p. 20). The study recommends further investigation of performance management in other departments of the university.